In silico analysis of Ffp1, an ancestral Porphyromonas spp. fimbrillin, shows differences with Fim and Mfa - Acuña Amador, Luis Alberto (2024)
Background. Scant information is available regarding fimbrillins within the genus Porphyromonas, with the notable exception of those belonging to Porphyromonas gingivalis, which have been extensively researched for several years. Besides fim and mfa, a third P. gingivalis adhesin called filament-forming protein 1 (Ffp1) has recently been described and seems to be pivotal for outer membrane vesicle (OMV) production. Objective. We aimed to investigate the distribution and diversity of type V fimbrillin, particularly Ffp1, in the genus Porphyromonas. Methods. A bioinformatics phylogenomic analysis was conducted using all accessible Porphyromonas genomes to generate a domain search for fimbriae, using hidden Markov model profiles. Results. Ffp1 was identified as the sole fimbrillin present in all analysed genomes. After manual verification (i.e. biocuration) of both structural and functional annotations and 3D modelling, this protein was determined to be a type V fimbrillin, with a closer structural resemblance to a Bacteroides ovatus fimbrillin than to FimA or Mfa1 from P. gingivalis. Conclusion. It appears that Ffp1 is an ancestral fimbria, transmitted through vertical inheritance and present across all Porphyromonas species. Additional investigations are necessary to elucidate the biogenesis of Ffp1 fimbriae and their potential role in OMV production and niche adaptation.